SANITASI DAN PEMANTAUAN JENTIK NYAMUK PADA TOILET SEKOLAH DASAR DI DESA SEI ROTAN KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG TAHUN 2013 - Astri Yosephin Sinaga; evi naria; nurmaini * (Lingkungan dan Kesehatan Kerja, 2014)
The toilet is one of facilities that there must be in the school. Toilet in many elementary school do not qualified standard especially sanitation which still below the standard. The toilet can be a source of desease. A tub of water is rarely cleaned can be a source of desease such a bacteria, virus, and others. The mosquito larva can be the cause of DBD is often found in water bath toilet that are rarely cleaned. In 2012 found that there is 7 cases of DBD, 2 of it child among 5-9 years old. This study aimed to find the toilets sanitation on toilets elementary school at Desa Sei Rotan Kecamatan Percut Sei Tuan Tahun 2013. Besides mosquito larva monitoring and counting the number of container index. This study was descriptive, to describe the sanitary toilets on elementary school and mosquito larva monitoring on toilet elementary school. Object of this study is sanitary toilets on elementary school totaling 44 toilets. This study did mosquito larva monitoring also. The study found from 44 toilets, 18 toilet (40%) have a good value while 26 toilet others (59,1%) have values than less good according to PERMENKES No. 1429 tahun 2006 about Pedoman Penyelenggaraan Kesehatan Lingkungan Sekolah. Container whom found larva is 5 from 44 toilets. So that it can be noted that the number of container index is 11,36 %. Puskesmas expected to perform the UKS schools, especially in the field of sanitary toilets in the form regular visits. The schools should pay more attention to sanitation toilets by creating regulations picket schoold with empowering disciples untick keep clean toilets and toilets fixtures complementin in the from of a trash can, desinfestan, brush, and broom. Keywords : The toilet, Elementary school. Mosquito larva, Sanitation